Proceedings 2nd National Workshop on Ocean Energy 2016 - National Workshop on Ocean Energy (2nd : 2016 : Kuala Lumpur); A. Bakar Jaafar, editor; Akbariah Mohd. Mahdzir, editor (Kuala Lumpur : UTM Ocean Thermal Energy Centre, Institute of Future Energy, Universiti Teknologi Malaysia, 2016)
Includes bibliographical references and index